Experimental study on the rotating detonation engine based on a gas mixture - Xue, Sainan; Zhang, Xin; Yang, Jianlu; Liu, Denghang; Ma, Hu; Zhou, Changsheng (Frontiers in Energy Research, 2023)
The direct connection test of a rotating detonation engine was carried out using a mixture of hydrogen, carbon monoxide and methane with a volume fraction of 5:4:1 as fuel and high enthalpy air as oxidizer. The outer and inner diameters of the annular combustors are 206 mm and 166 mm respectively. The mixed gaseous fuel is injected through small holes, and the air is injected through annular slots. The effects of combustor length, annular slot width and equivalent ratio on the formation, development, propagation and flameout of rotating detonation wave were analyzed, and several modes of rotating detonation were observed. It was found that when the width of the air annular slot was within the range of 3 to 5 mm, the pressure of detonation wave was augmented with the increase of the width of the slot. Further increasing the width cause unsteadity of detonation wave, and 6 mm was the critical condition for the formation of stable detonation. When the slot width of air was 4 mm and the combustor length was 160 mm, the propagation modes of detonation wave under different equivalent ratios all appeared the phenomena of the conversion between single and double wave, double wave collision and the conversion of propagation direction. When the equivalent ratio was 1.2 , the width slot of the air, which was within the range of 3 mm to 6 mm, was inversely related to the velocity of the detonation wave. When the width of the slot was 4 mm and the equivalent ratio was 1.0 to 1.2, which was positively correlated with the velocity of the wave. The length of the combustor was shortened to 80mm, the propagation mode of detonation wave was changed to single wave first and then double wave in the same direction. The velocity was reduced from 1130.69 m/s to 1024.16 m/s. The injectior used in the test inhibited the back pressure from the combustor.